The spreaded gracilis flap revisited: Comparing outcomes in lower limb reconstruction. Issue 8 (7th October 2017) - Heidekrueger, Paul Immanuel; Ehrl, Denis; Ninkovic, Milomir; Thiha, Aung; Prantl, Lukas; Herter, Frank; Mueller, Camillo; Broer, Peter Niclas
Abstract : Background: In lower limb reconstruction, the free gracilis muscle flap is usually chosen for coverage of small‐ to medium‐sized defects. Aim of this study was a re‐appraisal regarding the reconstructive indications of the gracilis muscle flap with a focus on postoperative complications in order to evaluate if it can also be routinely used to reconstruct large‐size lower limb defects. Methods: A total of 204 patients underwent free gracilis muscle transfers for lower limb reconstruction at our institution. Cases were divided according to the size of the defect into two groups (<150 cm 2 versus ≥150 cm 2 ). The small‐ to medium defect size group included 150 patients and the large defect size group included 54 patients. In the large defect size group, the muscle was enlarged as needed by careful dissection of the epimysium and all connective tissue surrounding the intrinsic vessels under loupe magnification to protect the muscle perfusion. Surgical complications were accounted for and the two groups compared accordingly. Results: Overall, there were no significant differences between the two groups of patients regarding the rate of major (15.72% versus 10.91%; P  = .506) and minor surgical complications (6.92% versus 3.64%; P  = .522). The total percentage of flap losses in the small to medium defect size group was 5.03%. There were no total flap losses in the large defect size group ( P  = .117). Conclusion: The use of the spreaded gracilis flap provides a valuable option for the microsurgeon, especially also to reconstruct large size lower limb defects.